Psychiatric illness in the medical profession: incidence in relation to sex and field of practice. - Watterson, D. J. (1976)
The overall incidence of psychiatric illness among the physicians of British Columbia during 1970-74 was 1.27% per year. The overall suicide rate was more than 36.5/100 000. Incidence was not dependent on sex or age. The two specialties with the highest incidence--ophthalmology and psychiatry--had previously been demonstrated to have significantly high rates of suicide. The highest incidence was among psychiatric residents; in other resident groups collectively the incidence was at the expected rate. Greater severity of illness and poorer prognosis was found in family physicians compared with specialists, although the incidence was the same in the two groups.